Platelet Mitochondrial DNA Methylation as Epigenetic Biomarker of Short-Term Air Pollution Exposure in Healthy Subjects - Sun, Huimin; Li, Yanting; Zhang, Jianzhong; Shi, Teng; Li, Xin; Cao, Xue; Wang, Tao; Kong, Nan; Pang, Yaxian; Bold, Tsendmaa; Zheng, Yuxin; Zhang, Rong; et al. (Frontiers in Molecular Biosciences, 2022)
Air pollution exposure is now considered a growing concern for global public health. RNA or DNA methylation changes caused by air pollution may be related to the development of cardiovascular disease. To investigate the early biomarkers of air pollution exposure, a panel study of eight college students recorded after a business trip from Qingdao to Shijiazhuang and back to Qingdao was performed in this work. The concentration of PM2.5, PM10, SO2, NO2, and CO in Shijiazhuang was higher than that in Qingdao during the study period. The platelet count was positively correlated with air pollutants of 0–6 day moving averages (βPM2.5 = 88.90; βPM10 = 61.83; βSO2 = 41.13; βNO2 = 57.70; βCO = 62.99, respectively, for an IQR increased). Additionally, internal dose biomarkers 2-OHNa, 1-OHNa, 2-OHFlu, 2,3-OHPhe, and ∑PAHs were also significantly associated with platelet count in participants. Furthermore, PM2.5 and PM10 are positively linked with methylation of one CpG site at platelet mitochondrial gene CO2 (PM2.5 = 0.47; PM10 = 0.25, respectively, for an IQR increase). Both platelet counts and methylation levels returned to their pre-exposure levels after leaving the highly contaminated area. In short, this study investigated the relationship between platelet properties and air pollution exposure, revealing that short-term exposure to air pollution might increase the risk of thrombosis. Our research suggests that platelet count and mitochondrial DNA methylation of mtCO2 site 2 in platelets from healthy adults may be the novel biomarker for acute exposure to air pollution.